Psychoeducation on Healthy Eating Patterns for Improving Elderly Quality of Life: Pendidikan Psikologis tentang Pola Makan Sehat untuk Meningkatkan Kualitas Hidup Lansia - Hanafi, Soraya; Laili, Nurfi (Indonesian Journal on Health Science and Medicine, 2025)
Background (general): The elderly often face health challenges due to biological aging, leading to decreased physical function and increased risk of chronic diseases.Specific background: An unhealthy diet among elderly populations contributes to conditions such as hypertension, diabetes, and high cholesterol, which diminish their quality of life.Knowledge gap: Limited psychoeducational interventions specifically address healthy eating patterns to improve quality of life among elderly individuals in community settings.Aims: This study aims to evaluate the effectiveness of psychoeducation in increasing knowledge of healthy eating patterns and improving quality of life among elderly participants.Results: Thirty elderly participants from Sepande Village, Sidoarjo, were involved in a one-group pretest-posttest design using a structured questionnaire. The findings demonstrated a significant increase in understanding of healthy eating patterns, with mean scores rising from 3.767 (pretest) to 7.900 (posttest). Additionally, improvements were observed in quality-of-life categories, with more participants achieving higher levels after psychoeducation.Novelty: This study provides empirical evidence that structured psychoeducation can enhance dietary knowledge and quality of life among the elderly, an area rarely explored in Indonesian community contexts.Implications: The results highlight the need for broader implementation of psychoeducation to support elderly well-being, and recommend further studies using stronger experimental designs for long-term evaluation. Highlights: Psychoeducation improved elderly knowledge of healthy diet. Quality of life increased after intervention. Community-based approach showed significant potential. Keywords: Psychoeducation, Elderly, Healthy Eating Patterns, Quality of Life, Community